An Eighteenth Century Joint Survey on the North-West Coast of America by British and Spanish Surveyors - David, Andrew (The International Hydrographic Review, 2010)
When the British surveying expedition under George Vancouver met a similar Spanish expedition under Dionisio Alcalà Galiano in June 1792 off Birch Bay, on the coast of present day USA state of Washington, they agreed to carry out a joint survey of the waters to the north of the Strait of Georgia. The resulting survey is a very early example of co-operation in hydrographic surveying between nations. It also highlighted the difficulties they encountered.